Characteristics of the Philosophical Approach in Education for the Teacher and the Leaner/ Khasâis al-Manhaj al-Falsafiy fi at-Tarbiyah wa at-Ta’lîm li al-Mua’allim wa al-Muta’allim - Huda, Ahmad Nawirul; Aini, Nur (Al-Manar, 2024)
The curriculum has a position as the heart of educational activities, which will guide and pump all educational activities towards achieving educational goals. Philosophy is also called the "parent" or "mother" of science or "Master Scientiarum". This research aims to determine the meaning of curriculum philosophy, the foundations of curriculum philosophy and the schools of curriculum philosophy. The research approach used by researchers is a qualitative approach using a library research approach. The data sources for this research are books, articles or newspaper articles related to the problem under study. The results of this research show that curriculum philosophy is a branch of philosophy that questions and discusses the basic concepts, goals, principles and values that underlie the design and implementation of curriculum in the educational context. The philosophical foundation of the curriculum includes the basic principles that form the basis of curriculum thinking and development. As well as several schools of curriculum philosophy that are commonly found, including: Idealism, Realism, Pragmatism and Existentialism.